Reducing Nares Acquired Pressure Injuries "Protect the Nares Because I Care" Project in Adult Inpatients: A Quality Improvement Project. Issue 5 (September 2021) - Sermersheim, Emily Read; Hall, Lillian; Boudreau, Lisa; Ambutas, Shirley; Gulczynski, Barbara
Abstract : PURPOSE: The purpose of this quality improvement (QI) project was to develop a preventive care bundle to reduce the incidence of nares acquired pressure injuries (NAPIs) to 3% in the adult inpatient population. PARTICIPANTS AND SETTING: Participants included adult inpatients in a large, Magnet-designated, 664-bed academic medical center in the Midwestern United States. APPROACH: Through our organization's "RUSH Way" QI model, we developed an evidence-based NAPI Bundle comprising a "T"-shaped hydrocolloid thin barrier, a tube holder securement device, patient assessments, and site checks. The project was initiated by a team of clinicians and administrators. An incidence report was conducted of hospital-wide existing NAPIs in 2015. A pilot QI project of the NAPI Bundle was implemented in the surgical intensive care unit (SICU) from January 2016 to May 2016 and then hospital-wide implementation began in June 2016. Data were collected on the incidence of NAPIs, and documentation of hydrocolloid dressing on the nose and intact, incidence of adverse events with hydrocolloid dressing, and hydrocolloid dressing changed every 3 days were evaluated. RESULTS: In 2015, the house-wide baseline NAPI incidence rate was 4.9%. Data from the SICU pilot confirmed Bundle effectiveness, as zero NAPIs occurred during the pilot period. The hospital-wide expanded pilot in 2016 showed the NAPI rate to be 3.2%, and in 2017, the incidence rate was reduced to 1.4%, well below the 3% goal. CONCLUSION: The NAPI Bundle implemented in our organization by RNs substantially reduced the incidence of adult inpatient NAPIs.